Langerhans cell histiocytosis of an intramammary lymph node in an 18-year-old woman - Ungari, Marco; Ferrero, Giuseppina; Varotti, Elena; Gusolfino, Marino Daniel; Manotti, Laura; Tanzi, Giulia; Trombatore, Monica; Bertoni, Ramona (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2020)
We describe an 18-year-old woman with several month’s history of a 12 x 7 mm palpable mammary nodule, that was hypoechoic, with regular margins and vascularization areas by ultrasound. A fibroadenoma was hypothesized (American College of Radiology BI-RADS 3). A 14 G needle biopsy was performed, showing a LC proliferation suspected for LCH of a lymph node, with florid dermatopathic lymphadenopathy in differential diagnosis. The multidisciplinary team of the breast clinic decided to perform a lumpectomy and a diagnosis of LCH involving an intra-mammary lymph node was made. Langerhans cells (LC) are dendritic cells characterized by grooved nuclei, irregular nuclear contours, and abundant cytoplasm, that normally reside in the skin and mucosal surfaces. They were positive for CD1a, langerin/CD207, and S100 by immunohistochemistry. Langerhans cell histiocytosis (LCH) is a clonal proliferation of histiocytes that is thought to be neoplastic in most cases. Reactive LC can be distinguished from LCH by cyclin D1 immunostaining, which is positive only in LCH. About 50% of cases have BRAF V600E mutations. The revised classification of histiocytes divides LCH in subtypes: LCH SS (single system), LCH lung positive, LCH Multiple System/Risk Organ negative and LCH Multiple System/Risk Organ positive. Localized disease can progress to multisystem involvement. The diagnosis of LCH is based on clinical and radiological findings in combination with histopathological, immunophenotypic or ultrastructural analyses identifying tissue infiltration by LC. It is recommended that biopsy confirmation of suspected LCH be performed in all cases. Lymph nodes may be the only site of disease or a part of multisystem involvement by LCH. The histologic differential diagnosis is discussed.